The Effects of Nurses' Attitudes and Behaviors Toward End-of-life Care on Clinical Decision-making - Saadet Erzincanlı; Kadriye Sayın Kasar (Galenos Yayinevi, 2022)
Objective:This study aimed to determine the effects of nurses' attitudes and behaviors toward end-of-life care on clinical decision-making.Materials and Methods:This descriptive and cross-sectional study was conducted between April 2019 and August 2019 with 84 nurses who work in the intensive care units of a training and research hospital. Data were collected using the Individual Introduction Form, the Scale of the Attitudes and Behaviors of Intensive Care Nurses Intended for End-of-Life Care, and the Clinical Decision-Making Scale in Nursing.Results:The mean age of the intensive care nurses who participated in the study was 33.13±5.79 years. Of whom, 89.3% were females and 64.3% were undergraduate. The total mean score of the Scale of the Attitudes and Behaviors of Intensive Care Nurses Intended for End-of-Life Care was 57.91±10.53 and 140.64±23.52 for the Clinical Decision Making in Nursing Scale. The total mean score of the Scale of the Attitudes and Behaviors of Intensive Care Nurses Intended for End-of-Life Care of nurses with a master of education level was significantly higher. Additionally, the total mean score of the Clinical Decision Making in Nursing Scale of nurses who received training for end-of-life care was higher, with a positive low-level relationship with the Scale of the Attitudes and Behaviors of Intensive Care Nurses Intended for End-of-Life Care.Conclusion:Therefore, the nurses' attitudes and behaviors toward end-of-life care have low-level relationship and effects on the clinical decision-making level.